METHODOLOGICAL APPROACHES TO THE TRAINING OF FUTURE DENTISTS FOR PROFESSIONAL ACTIVITIES (Physical Culture and Sport: Scientific Perspective, 2023)
The article examines the questions of the formation of professional competence of future dentists in the context of training for professional activities with an emphasis on the theoretical and methodological basis, which is expressed in specific methodological approaches. Each of the approaches (systemic, activity-based, person-oriented, integrative, competence-based) allows you to consider the process of forming the professional competence of future dentists from different positions. Taking into account the constant challenges in different spheres of our country's life and taking into account the state of war, the labor market requires training of future specialists who would have a high level of knowledge and practical skills, could make quick, clear and not always standard decisions in different life situations, be responsible in their professional occupation. Based on a review of scientific sources, different approaches to defining the concepts of «professional competence» were considered. Theoretical and practical aspects of the problem were defined.The quality of providing dental care to the population is directly related to the creation of conditions for professional development, which in turn can be achieved by guaranteeing a decent level of training at the current stage of the development of educational technologies. A sign of a modern dentist is the ability to work in a team, to have knowledge of human psychology, to be legally knowledgeable using knowledge of medical law in practice. Knowledge and fluency in foreign languages for opportunities for self-education through attendance at foreign educational events, study of scientific sources published in a non-Ukrainian language are important competencies that must be used by a dentist. The development of informatization has also widely covered dentistry, the constant appearance of new devices and software updates for them obliges one to navigate and master the skills of working with them. It is also important for the future dental specialist to develop the ability to make decisions based on the principle of evidence-based medicine.Ensuring such conditions is a step on the way to quality formation of professional competence of future dentists in the context of preparation for professional activities.
Keywords: professional competence; training of dentists; methodological approach; system approach; person-oriented approach; formation; activity approach; integrative approach; competence approach